Linking Service Quality To Customer Loyalty: The Mediating Role of Trust and the Moderating Role of Religiosity - Primananda, Naufal Athiya; Asyhari; Othman, Azmahani Yaacob (Jurnal Aplikasi Manajemen, 2025)
Islamic banking in Indonesia, despite showing significant growth, faces challenges in building strong customer loyalty. Understanding the factors that drive customer loyalty, such as service quality, trust, and satisfaction, is crucial. However, previous research has often overlooked the role of religiosity in a business context as a potential driver of customer loyalty. This study aims to analyze the relationship between service quality, trust, satisfaction, and customer loyalty in Islamic banking. Furthermore, to examine the moderating role of student religiosity in enhancing Sharia customer loyalty. This study employed a quantitative approach with a survey method. The study population was students at Sultan Agung Islamic University, and a sample of 376 respondents was selected using proportional sampling. Primary data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that service quality has a positive influence on consumer satisfaction, and in turn, on customer loyalty. Furthermore, customer satisfaction positively influences trust, and trust positively impacts customer loyalty. In addition, the findings evidence that religiosity can moderate the relationship between trust and customer loyalty, meaning that higher levels of religiosity can strengthen the effect of trust on loyalty. The contribution of this research lies in testing the moderating role of religiosity to fill the empirical gap and the use of Muslim students as respondents, which has never been used before. This study offers theoretical implications with a new perspective on the role of religiosity in Islamic banking, with an Islamic student perception approach. The managerial implication provides new insights into how customer trust, satisfaction, and loyalty can be strengthened through consumer religiosity.